2023
DOI: 10.3934/gf.2023008
|View full text |Cite
|
Sign up to set email alerts
|

Insuring a greener future: How green insurance drives investment in sustainable projects in developing countries?

Abstract: <abstract> <p>Insurance companies are responding to the global challenge of climate change by introducing green insurance policies, which aim to promote sustainable projects across the globe. These policies offer financial protection and coverage for initiatives related to renewable energy, energy efficiency and other sustainable endeavors. Moreover, they incentivize investment in these projects by providing lower premiums or other financial benefits. In order to assess the impact of green insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Through theoretical analysis, many scholars have found that GI plays a positive role not only in strengthening enterprise environmental risk management (Yang and Zhang, 2022) but also in accelerating the layout of green industries (Mills, 2003) and promoting innovation in green technologies (Hu et al, 2023). It can continuously enhance public and societal environmental awareness (Brogi et al, 2022), guide the direction of social funds (Desalegn, 2023), and promote the improvement of regional EQ. On the other hand, a minority of scholars, through empirical research, have delved into the impact of GI on EQ.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through theoretical analysis, many scholars have found that GI plays a positive role not only in strengthening enterprise environmental risk management (Yang and Zhang, 2022) but also in accelerating the layout of green industries (Mills, 2003) and promoting innovation in green technologies (Hu et al, 2023). It can continuously enhance public and societal environmental awareness (Brogi et al, 2022), guide the direction of social funds (Desalegn, 2023), and promote the improvement of regional EQ. On the other hand, a minority of scholars, through empirical research, have delved into the impact of GI on EQ.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akomea-Frimpong et al (2022) found reluctance among building owners and construction firms to replace conventional practices by green building and financing practices. Desalegn (2023) addressed the need for the insurance industry to be more active in providing complete green insurance building coverage.…”
Section: Insufficient Social Acceptance From Different Stakeholdersmentioning
confidence: 99%